Carbon Nutrition in Rooting of Nodal Cuttings in Eucalyptus tereticornis Smith (Mysore Gum) - Bakshi, Meena; Kaur, Manpreet (Indian Forester, 2018)
Complex interplay of external and internal factors affects the process of root induction and development of plant system. Auxins, a phytohormone, play an important role not only in the initiation of root meristem but also in enhancing the root number. Auxins help in rooting process by making carbohydrates available at the base of the cuttings. The present study was undertaken to study the dynamics in carbohydrate content in rooting zone of nodal cuttings of Eucalyptus hybrid treated with different concentrations of indol butyric acid (IBA). The results revealed that the sugars accumulated in the basal segments during 15 days period was significantly greater in the IBA treated cutting than those of the control cuttings. Maximum sugar content was observed in cuttings of IBA 4000ppm treated. There was further increase in the content of reducing sugars at 30 days, the level in IBA 4000ppm being almost twice that of control. The IBA 4000ppm and control showed an increase in sugar content whereas IBA 2000ppm cuttings depicted decline in reducing sugar after 45 days of planting which could probably be due to its utilization in the rooting process envisaging thus that for rooting in Eucalyptus, auxins play crucial role by augmenting the flow of carbohydrates.